Clinical Characteristics of COVID-19 Pneumonia Patients in Abdoel Moeloek Regional Public Hospital, Bandar Lampung, Indonesia. - Soemarwoto, Retno AS; Marlina, Nina; Mustafa, Syazili; Sukarti, Sukarti; Sinaga, Fransisca; Gozali, Ahmad; Hapsari, Tantri Dwi KR; Hidayat, Hidayat (Fakultas Kedokteran, 2020)
a novel coronavirus (SARS-CoV-2) causes a new, really infectious viral disease named COVID-19. This infection quickly develops into a pandemic and it is becoming a major problem in the world. Pneumonia is a severe and dangerous complication of the disease. In this study, we aimed at exploring the clinical characteristics of the COVID-19 pneumonia. A retrospective single-center study in Abdoel Moeloek Hospital of Lampung Province was conducted on March to May 2020. It enrolled 12 Hospitalized patients with confirmed COVID-19 pneumonia by real-time RT-PCR. The purpose of this study was to investigate and describe the features of this epidemic disease. The clinical features, laboratory findings and chest X-ray images of them were reviewed and analyzed. Consecutive patients with COVID-19 pneumonia were included in the study. There were 7 patients who recovered while 5 of them died. Most of them were male (10 patients or 83%) and they were about 40 years (9 patients or 75%). Most of patients (75%) had comorbid disease such as hypertension, diabetes, hepatitis, obesity, and heart disease and they also had a history of travel from infected area. They who died (5 patients or 100%) had comorbid diseases. The patients main complaints were cough and shortness of breath (12 patients or 100%), subfebrile fever (9 patients or 75%), diarrhea (5 patients or 42%), abdominal pain nausea and vomiting (4 patients or 33%). Related to laboratory examination, they got decreasing of calcium level (11 patient or 91%), lymphocytes (9 patients or 75%), hemoglobin level (8 patients or 67%) and albumin levels (7 patients or 58%). On the contrary, they got increasing of the level of the erythrocyte sedimentation rates (12 patients or 100%), the level of C-reactive protein (11 patients or 91%), physiological coagulation (12 patients or 100%), D-dimers plasma levels (10 patients or 83%), liver enzymes test (9 patients or 75%), leukocytes (7 patients or 57%), and chloride (6 patients or 50%). In the chest X-ray interpretations, we found that most of cases ( 10 patients or 83%) were bilateral pneumonia and they occurred massively in the inferior lobe of the lung. On the death cases, they were found consolidation in both lower lung fields. The clinical data, laboratory and radiological examination of patients with COVID-19 pneumonia showed both inflammation and coagulopathy. A decreased lymphocyte count and plasma calcium level, and an increased high-sensitivity C-reactive protein level and D-dimer plasma level were the most common laboratory findings. The infection caused severe acute respiratory syndrome and it was correlated to high mortality. High efforts are needed for further studies to fulfill the gap in knowledge of this disease.Key words: COVID-19 pneumonia, clinical manifestation, laboratory findings, chest X-ray, SARS-CoV-2,